2017
DOI: 10.12681/eh.11579
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary inventory of scale insects on mango trees in Benin

Abstract: A preliminary inventory of scale insects (Hemiptera: Coccoidea) developing on the mango tree is presented for Northern and Central Benin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…As for I. aegyptiaca, it was also observed in West Africa, Asia and Oceania [11]. Species diversity of mango mealybugs revealed in this study is relatively limited as compared to the 10 species of the same families reported on the mango tree in the North and Central regions of Benin [9]. Ferrisia virgata and I. aegyptiaca populations' densities were very low during the study period.…”
Section: Discussionmentioning
confidence: 55%
“…As for I. aegyptiaca, it was also observed in West Africa, Asia and Oceania [11]. Species diversity of mango mealybugs revealed in this study is relatively limited as compared to the 10 species of the same families reported on the mango tree in the North and Central regions of Benin [9]. Ferrisia virgata and I. aegyptiaca populations' densities were very low during the study period.…”
Section: Discussionmentioning
confidence: 55%
“…Further, secretions of extra-floral and floral nectars by host plants and the presence of hemipteran trophobionts on these host plant may favor the development of the ants (Kenne et al, 2003). Mango trees in the Sudanian area of Benin were reported to harbor large numbers of scale insects (12 species) particularly on mango fruit petioles and on the fruits (Germain et al, 2010). In contrast, Vayssières (2012) recorded only two Hemiptera species on cashew in northern Benin.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, Pellizzari (2007) reports that C. aonidum, although it was already registered as an enemy of Dracaena and Kent'ta in greenhouses, it was found to be acclimatized in Calabria on citrus outdoors in 2006. It is also recently IS ENTOMOLOGIA HELLENICA 16 (2005-2006 reported as a new pest in greenhouses in (Germain and Matile Ferrerò 2005) and the Hungary (Reiderne and Kozàr 19941. France Netherlands (Jansen 2004 families Cucurbitaceae and Solanaceae, but during this study, the possibility to infest fruits of C. maxima (Cucurbitaceae) and tubes of S. tuberosum (Solanaceae) was recorded in the laboratory.…”
Section: Discussionmentioning
confidence: 99%